Fenomena Sosial Tukang Parkir di Kota Makassar: Analisis Peran Ekonomi dan Implikasinya Terhadap Ketertiban Sosial - Sri Wahyuni; Rahmadani Islawiyah; Riska; Lukman Ismail (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The phenomenon of informal parking attendants is a growing social reality in line with increasing urban mobility and limited formal employment opportunities. The presence of parking attendants in Makassar not only serves as a source of livelihood for marginalized groups but also raises issues of social order and the use of public space. This study aims to analyze the economic role of parking attendants and their implications for social order in urban spaces. The study employed a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with seven informants five parking attendants and two parking service users and field observations at several parking activity points. Data were analyzed using thematic reduction, presentation, and conclusion-drawing techniques. The results indicate that informal parking activities have become a primary survival strategy due to limited education and access to formal employment. This practice results in narrowing traffic space, uncertainty about fares, and potential disruption to social order. This study concludes that the phenomenon of parking attendants is a structural problem that requires integrative management policies, not just a regulatory approach. Therefore, adaptive regulations are needed that can accommodate the economic needs of informal workers while maintaining order in urban spaces.